2016
DOI: 10.1073/pnas.1519994113
|View full text |Cite
|
Sign up to set email alerts
|

Sp5 and Sp8 recruit β-catenin and Tcf1-Lef1 to select enhancers to activate Wnt target gene transcription

Abstract: The ancient, highly conserved, Wnt signaling pathway regulates cell fate in all metazoans. We have previously shown that combined null mutations of the specificity protein (Sp) 1/Klf-like zinc-finger transcription factors Sp5 and Sp8 (i.e., Sp5/8) result in an embryonic phenotype identical to that observed when core components of the Wnt/β-catenin pathway are mutated; however, their role in Wnt signal transduction is unknown. Here, we show in mouse embryos and differentiating embryonic stem cells that Sp5/8 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 36 publications
8
73
0
Order By: Relevance
“…Multiple signaling pathways are involved in the EMT process, including WNT/β-catenin signaling, TGF-β signaling and Notch signaling. 70-73 One important feature of EMT is the down-regulation of Cadherin 1 (CDH1, also known as E-cadherin) by ZEB1 and ZEB2. In the present study, we observed that expression of CDH1 was down-regulated from day 4 to day 30 (Online Figure X A-B).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple signaling pathways are involved in the EMT process, including WNT/β-catenin signaling, TGF-β signaling and Notch signaling. 70-73 One important feature of EMT is the down-regulation of Cadherin 1 (CDH1, also known as E-cadherin) by ZEB1 and ZEB2. In the present study, we observed that expression of CDH1 was down-regulated from day 4 to day 30 (Online Figure X A-B).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, genome-wide surveys of TCF or β-cat binding in vertebrates reveal the presence of several TF binding site motifs besides the TCF site consensus 1, 30, 39, 77, 78 . Other TFs have been reported to co-localize with TCFs 36, 38, 39, 79, 80 , and in the cases of Cdx2 79 , Sp5/8 81 , and TEAD TFs 82 , a co-dependency with TCFs or β-cat for chromatin association has been reported. In addition, TCF binding to chromatin is highly cell type specific 36 and is dynamic over time in the same cell type 38, 39 .…”
Section: Tcfs and Wnt Target Locationmentioning
confidence: 97%
“…If this were the case, we would expect Slc7a5 to be lost in embryos in which the b-catenin downstream transcription factors Sp5 and Sp8 are mutated, as these embryos also fail to form paraxial mesoderm [69]. Indeed, available ChIP-seq data show that while Sp5 and Sp8 bind to early mesodermal genes, they do not target Slc7a5 in differentiating mouse ESCs [70]. This finding indicates that Slc7a5 expression in the neural tube does not depend on signals from the newly formed paraxial mesoderm and further that Slc7a5 is regulated by b-catenin downstream transcription factors other than Sp5 and Sp8.…”
Section: Sox10mentioning
confidence: 99%